A case study of lateral epicondyle pain in a cricketer: a clinical reasoning approach to management. - Griffiths H; Phillips N (Physical Therapy in Sport, 2003)
The differential diagnosis of musculoskeletal disorders in general, and sports injuries in particular, is complex, as they often present interdependent pathological and aetiological processes. Clinical reasoning is a powerful tool that can allow effective differential diagnoses to be made and consequently successful outcomes achieved. It is a hypothetic-deductive reasoning process that encompasses pattern recognition and pathognomonic signs (Jones, 1995). This case study explores its use in the diagnosis and management of a sports injury. It demonstrates the application of the clinical reasoning process by outlining the reasoning underpinning the generation and testing of hypothesis and the re-evaluation that is performed following intervention. During this it considers the contributions and interactions of the physical, neurogenic, psychological and physiological systems, and additionally highlights the importance of active involvement of all parties in achieving a successful outcome.